(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In this paper we explore about the actions of keycharacters in Shakespeare’s Titus Andronicus. In Shakespeare’s TitusAndronicus, Tamora and Lavinia rebel against their society because of themisogyny and oppression that they suffer. Titus Andronicus is a difficultplay for modern audiences to enjoy because of the violence and the apparentlack of positive female figures